Genetic Variation of Growth and Wood Density in a Progeny Test of Rubroshorea leprosula in Central Kalimantan - Ariesya Kurnia Dewi; Sapto Indrioko; Mohammad Na'iem (Jurnal Hutan Tropis, 2026)
One approach to reducing the rate of degradation and selecting superior genotypes for genetically improved plantations is the establishment of progeny test plantations. Rubroshorea leprosula is a potential species for progeny testing based on its growth performance and wood quality. The research objective was to evaluate the genetic variation and genetic parameters in progeny test of R. leprosula at PT. Sari Bumi Kusuma in Central Kalimantan, providing a basis for selection and breeding strategies. The experiment was arranged in a RCBD with five replicate blocks. Each block had 80 families (seedlot), with 4 trees per family. Growth characteristics (diameter, height, and bole height) and  wood density were analyzed. Wood density was estimated using the Pilodyn penetration method. The results indicated significant genetic diversity between families for all measured traits. The estimated family heritability ranged from 0.025 – 0.320, was categorized as low to moderate across traits, suggesting a considerable environmental influence on trait expression. A robust and favorable genetic correlation recorded between diameter and height, as well as height and bole height. However, a negative correlation was observed within diameter and wood density, indicating a trade-off between the two. Multi-trait selection revealed that genetic gain based on a three-trait index (excluding wood density) was higher than that based on a four-trait index. A moderate selection intensity (30%) is indicated to establish a balance between genetic gain and genetic variety preservation.